Data for “Negative ecological impacts of honeybees begin at densities below recommended levels for crop pollination” - Ainhoa Magrach (4044062) (2025)
This dataset supports a meta-analysis examining the ecological consequences of varying managed honeybee (Apis mellifera) hive densities on pollinator communities, plant-pollinator interactions, and crop yields. The data were compiled from peer-reviewed studies published globally and include information on study location, hive density, pollinator richness and abundance, visitation rates, fruit/seed set, and other relevant ecological metrics. Each entry includes: Study reference Experimental design Hive density (hives/ha) Response variables (e.g., pollinator richness, fruit yield) Effect sizes (Hedges’ g) Sample sizes and variance estimates The data have been cleaned, standardized, and formatted for statistical synthesis, and were used to identify density thresholds associated with significant ecological disruptions.